HAECCEITAS, QUIDDITAS E FORMALITAS NELLE RIFLESSIONI DI GIOVANNI DUNS SCOTO - Scozia, Matteo (Thaumazein: Revista Online de Filosofia, 2015)
In this article, assuming Antonie Vos’ analytical interpretation of John Duns Scotus’ ontological system, I present Scotus’ theory of haecceitas, quidditas and formalitas. Considering an hypothetical res existing in the real (interpreted by a real approach to modal possible worlds semantic), I will try to explain that there are several degrees of the real for which haecceitas is the element that permits to individuate the same res in every existential condition, i.e. through possible worlds; quidditas is a particular and contingent kind of universal valid just in one world; formalitas is the necessary kind of universal, valid in all worlds.